GreenSeeker™and the diagnosis of crop health. - Gutiérrez-Soto, Marco V. (2011)
Theobjective of this note is to provide basic information and technicalprinciples needed for the use of the GreenSeeker™,in agricultural applications such as nitrogen fertilization,irrigation scheduling, mapping of agricultural fi elds andprecision agriculture. A description of the instrument is provided,as well as the technical and physiological principlesthat support its use in agriculture. The radiative propertiesof plant canopies and light refl ection from healthy andstressed crops are described briefl y. Possible applications ofGreenSeeker in diagnosis and correction of crop disordersin the fi eld in real time are considered, according to spatialheterogeneity ubiquitous in tropical agro ecosystems. Thelimitations of the technology currently available and itsapplications to other tropical crops, besides rice and corn,are also addressed.